Pembuatan Sistem Rumah Pintar dengan Voice Assistant di Raspberry Pi - Felix Hartono; Resmana Lim; Lily Puspa Dewi (Jurnal Infra, 2020)
At this day, the IoT (internet of Things) has been become a trend that keep going in the middle of society. The expansion of IoT that happen really fast open many potency from the previous technology never seen before, including smart home. Smart home is a bunch of sensors that connect with each other and can be controlled through the internet to watch the condition inside or outside home. The purpose of smart home is to elevate the quality of live for the owner of the house with connecting the sensors and other smart object that can be controlled and accessed through mobile device or computer.It is the same with voice assistant that now is in fast developing state. In everyday life, it is common for use to interract with one of many voice assistant that already exist like Alexa from Amazon, Siri from Apple, Google's Assistant from Google and many more. This system can control the house with 2 microcontroller, which is Raspberry Pi 3 and Wemos D1 mini ESP8266. Both of microcontroller can be controlled with voice command and through website. For controlling using the voice command can be used by saying words that contains keywords to run the command. The voice command can be done with 5 Meters range from microphone. The user can also say the words with uncorrect grammar or uncorrect words as long as those words has keywords to run the command, the command will be run. After that this system can controll the device that has IR Receiver with using IR LED and command that already been stored. As long as the device can connect with relay or has IR Receiver, then the device can be controll by the system or the user from anywhere.